Evaluation of Serum Leptin and Ferritin Levels in Females with Beta Thalassemia Major - A. Abdulhaleem, Fatima; Hussein J. Al-Qaisi, Alaa; M. Jamil, Dalia; M. Redwan, Amamer; Wahida Zulkifli, Nur (Al-Nahrain Journal of Science, 2025)
Beta thalassemia is an inherited blood disorder caused by inadequate or absence synthesis of β-globin chains. It is classified into three subgroups: β-thalassemia minor, β-thalassemia intermedia, and β-thalassemia major. Beta thalassemia patients suffer from chronic hemolytic anemia and consequently, require frequent blood transfusions, which however can cause iron overload in tissues and organs. The accumulation of iron can cause severe complications such as endocrine dysfunction and chronic liver diseases. Leptin, a polypeptide hormone secreted by adipose tissue and plays an important role in maintaining body weight. This study aimed to evaluate serum leptin and ferritin levels in females with beta thalassemia major. The study included 35 splenectomized thalassemia patients and 35 healthy controls. Anthropometric profile, hematological profile, and serum ferritin and leptin levels were determined for all participants. The results showed a significant decrease in body mass index (BMI), red blood cell (RBC), hemoglobin (Hb), hematocrit (Hct), mean corpuscular volume (MCV), and leptin in thalassemia patients compared to the healthy controls. In contrast, there was a significant increase in serum ferritin in thalassemia patients compared to the healthy controls. It is concluded that patients with beta thalassemia major had considerably lower serum leptin levels. The increased blood ferritin levels in these patients suggest that the malfunction of adipose tissue brought on by iron overload is probably linked to this drop in leptin.